Single-use negative-pressure wound therapy versus conventional dressings for closed surgical incisions: systematic literature review and meta-analysis. Issue 1 (17th January 2021) - Saunders, C; Nherera, L M; Horner, A; Trueman, P
Abstract: Background: Surgical-site complications (SSCs) remain a significant cause of morbidity and mortality, particularly in high-risk patients. The aim of this study was to determine whether prophylactic use of a specific single-use negative-pressure wound therapy (sNPWT) device reduced the incidence of SSCs after closed surgical incisions compared with conventional dressings. Methods: A systematic literature review was performed using MEDLINE, Embase and the Cochrane Library to identify articles published from January 2011 to August 2018. RCTs and observational studies comparing PICO™ sNPWT with conventional dressings, with at least 10 patients in each treatment arm, were included. Meta-analyses were performed to determine odds ratios (ORs) or mean differences (MDs), as appropriate. PRISMA guidelines were followed. The primary outcome was surgical-site infection (SSI). Secondary outcomes were other SSCs and hospital efficiencies. Risk of bias was assessed. Results: Of 6197 citations screened, 29 studies enrolling 5614 patients were included in the review; all studies included patients with risk factors for SSCs. sNPWT reduced the number of SSIs (OR 0.37, 95 per cent c.i. 0.28 to 0.50; number needed to treat (NNT) 20). sNPWT reduced the odds of wound dehiscence (OR 0.70, 0.53 to 0.92; NNT 26), seroma (OR 0.23, 0.11 to 0.45; NNT 13) and necrosis (OR 0.11, 0.03 to 0.39; NNT 12). Mean length of hospital stay was shorter in patients who underwent sNPWT (MD −1.75, 95 per cent c.i. −2.69 to −0.81). Conclusion: Use of the sNPWT device in patients with risk factors reduced the incidence of SSCs and the mean length of hospital stay. Abstract : A systematic literature review and meta-analysis was performed for a specific single-use negative-pressure wound therapy (sNPWT) device to determine whether there were improvements in outcomes compared with conventional dressings. Odds of surgical-site infection, dehiscence, seroma and necrosis were reduced by 63, 30, 77 and 89 per cent respectively. There was a 1.75-day reduction in length of hospital stay in favour of sNPWT. Reduces SSI in patients with risk factors